The Pararectus Approach in Acetabular Surgery: Radiological and Clinical Outcome. Issue 2 (February 2020) - Wenzel, Lisa; von Rüden, Christian; Thannheimer, Andreas; Becker, Johannes; Brand, Andreas; Augat, Peter; Perl, Mario
Abstract : Objectives: To evaluate radiological fracture reduction and clinical results using the pararectus approach in complex acetabular fractures involving the anterior column. Design: Retrospective database analysis of prospectively collected data. Setting: Level 1 trauma center. Patients/Participants: 61 patients (48 male and 13 female) with a median age of 55 (range 17–91) years were included. According to the chosen surgical approach, they were divided into 2 groups. The P-group included 43 patients, among them 32 male and 11 female patients with a median age of 55 (range 17–90) years. Eighteen patients [16 male, 2 female; median age: 53 (range 23–91) years] were treated through the ilioinguinal approach (I-group). Intervention: Anterior surgical procedures through the pararectus or the ilioinguinal approach. Main Outcome Measured: Reduction results were rated according to the modified Matta criteria using a measurement protocol of hip joint gaps and steps in computed tomography scans. Operation time, complications, and clinical outcomes median one year postoperatively were compared. Results: In the pararectus group reduction was anatomical in 21 out of 40 analyzed patients (52.5%), imperfect in 11 patients (27.5%), and poor in 8 patients (20%). The mean joint step reduction was 3.7 mm, and the mean joint gap reduction was 12.1 mm. In the ilioinguinal group reduction was anatomical in 9 out of 18 patients (50%), imperfect in 4 patients (22%), and poor in 5 patients (28%). The mean joint step reduction was 1 mm, and the mean joint gap reduction was 7 mm. Operation time was significantly shorter in the P-group (mean: 49 minutes; P < 0.001). Conclusions: This study indicates that acetabular fracture reduction using the pararectus approach is at least comparable with the ilioinguinal approach independent of patients' age. A relevant advantage of the pararectus approach was seen in a significantly shorter operation time. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.